Riskante Leben? Geschlechterordnungen in der Reflexiven Moderne. (Verlag Barbara Budrich, 2012)
Individualisation processes and the redistribution of social risks do not leave traditional gender relations untouched. The contributions in this volume examine the changes that (can) arise for gender identities, gender relations and gender-typical positioning in society.